2013
DOI: 10.4103/0972-3919.116814
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metastases as the initial manifestation of an unknown primary lung cancer detected on F-18 fluorodeoxyglucose positron emission tomography/computed tomography

Abstract: Skeletal muscle metastasis as the initial presentation of the unknown primary lung cancer is unusual. A 65-year-old male patient presented with pain and swelling of the right forearm. Fine needle aspiration of the swelling revealed metastatic squamous cell carcinoma. The patient underwent whole body F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) to identify the site of the primary malignancy. The authors present PET/CT images showing FDG-avid metastases to the skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…An isolated, painful skeletal muscle metastasis as the initial manifestation of an otherwise asymptomatic primary malignancy, as in our patient, is uncommon [ 6 , 9 , 14 ]. Muscular metastases typically present as a painful and frequently palpable mass with or without localized swelling [ 2 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An isolated, painful skeletal muscle metastasis as the initial manifestation of an otherwise asymptomatic primary malignancy, as in our patient, is uncommon [ 6 , 9 , 14 ]. Muscular metastases typically present as a painful and frequently palpable mass with or without localized swelling [ 2 ].…”
Section: Discussionmentioning
confidence: 98%
“…A subgroup analysis revealed that masses of pulmonary origin had low central attenuation with rim enhancement as the most common finding on CT [ 13 ]. Correlation with FDG-PET is recommended in all patients with a history of malignancy or a suspicion lesion [ 3 , 8 , 9 , 18 ]. Biopsy of these masses is mandatory for proper diagnosis and further management [ 6 , 9 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites of skeletal muscle metastasis of lung cancer are the thigh, iliopsoas, and paraspinous muscles. Lesions have also been reported in the orbit and pectoral muscles [7][8][9][10]. Besides, some literature also reports the calf muscles being among the common spreading sites [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, metastasis to skeletal muscles is well documented in nonsmall cell lung cancer (NSCLC). [ 1 2 ] Further, skeletal muscle metastasis (SMM) reflects and aggressive disease and patients with multiple muscle metastases have bad overall survival rates as compared to solitary muscle metastasis. [ 3 ] Lung carcinoma is a common cause of cardiac metastasis.…”
Section: Discussionmentioning
confidence: 99%